Performance of Oily Water Separator at KMP. Merak in Efforts to Prevent Pollution - Sufriyadi; Miran; Achmat, Baso; Syamsu (Dinasti Publisher, 2025)
The sea is a vital ecosystem that supports human life and marine biodiversity. However, marine pollution caused by the discharge of oily waste from ships remains a significant environmental issue, despite the existence of national and international regulations. This study aims to examine the performance of the Oily Water Separator (OWS) on the vessel KMP Merak in preventing marine pollution. A qualitative research approach was employed through observation, interviews, and literature review. The findings indicate that several factors influence OWS performance, including clogged coalescer filters, sludge accumulation in the engine bilge, lack of spare parts, and the absence of a structured maintenance system. A decline in OWS performance can lead to marine pollution, ecosystem damage, and disruption of the marine food chain. Solutions include regular maintenance, proper machine monitoring, well-organized spare part management, and maintaining sufficient air pressure in the three-way valve system. This research highlights the importance of consistent and disciplined OWS maintenance as a commitment to preserving the marine environment. The study is expected to serve as a reference for increasing awareness among ship crews and related institutions in the proper operation and maintenance of OWS equipment.